Viability of a practical multicyclic sorption-based water harvester with improved water yield. (1st March 2022) - Wang, Wenwen; Pan, Quanwen; Xing, Zheli; Liu, Xueying; Dai, Yanjun; Wang, Ruzhu; Ge, Tianshu
Highlights: A multicyclic sorption-based water harvester was designed and tested on an island. Two-cycle AWH design for potential large-scale deployment of water generation. The device effectively delivered water under a regeneration temperature of 51 °C. Multicycle realized 0.42 kgwater kgadsorbent −1 and a thermal efficiency of 32.2%. Abstract: Sorption-based atmospheric water harvesting (SAWH) has emerged as an attractive way to relieve water scarcity. However, the daily water yield of currently reported SAWH devices remains low to satisfy the rising demand for drinking water. The sorption and desorption kinetics, long-term stability and especially facile scaling-fabrication of adsorbents and scaled-up device implementation have become the bottleneck to such large-scale SAWH application. To overcome these challenges, an air-cooled SAWH device was fabricated to investigate its atmospheric water harvesting (AWH) performance under real island climate and its feasibility of multicyclic operation. Under monocyclic operation, the device demonstrated the superior water productivity as much as 3.9 kg day −1, or 0.39 kgwater kgadsorbent −1 day −1, at 31 °C and 70% RH, with a thermal efficiency of 25.4% (desorption at 94 °C). The SAWH device demonstrated successful water production through 2 adsorption-desorption cycles within one day, with increased thermal efficiency to as high as 32.2% and increased water harvesting performance up to 0.42 kgwater kgadsorbent −1 day −1 by 20–90%. This is the first demonstration in multicyclic SAWH at large scales, holding the promise of large-scale and practical water supply in island areas while opening up new applications such as indoor dehumidification. Graphical abstract: Image, graphical abstract